A Comparison of Outcomes between the Wiltse Approach with Pedicle Screw Fixation and the Percutaneous Pedicle Screw Fixation for Multi‐Segmental Thoracolumbar Fractures - Yadong Zhang; Wentao Wang; Lulu Bai; Dingjun Hao (Orthopaedic Surgery, 2023)
Objective Multi‐segmental thoracolumbar fracture (MSF) generally refers to fractures occurring in two or more segments of the thoracolumbar spine. With the development of minimally invasive concept, there is little research on its application in the field of MSF. The purpose of this study is to compare two minimally invasive surgical techniques and determine which one is more suitable for treating patients with neurologically intact MSF. Methods We retrospectively analyzed the clinical data of 49 MSF patients with intact nerves who were admitted from January 2017 to February 2019. Among them, 25 cases underwent percutaneous pedicle screw fixation (PPSF), and 24 cases underwent Wiltse approach pedicle screw fixation (WAPSF). The operation time, number of fixed segments, blood loss, length of incision, postoperative ambulation time, accuracy of pedicle screw placement, facet joint violation (FJV), number of C‐arm exposures, as well as pre‐ and postoperative visual analogue scale (VAS), Oswestry disability index (ODI), local Cobb's angle (LCA), and percentage of anterior vertebral body height (PAVBH) were recorded for both groups. Paired sample t‐test was used for intra‐group comparison before and after surgery while independent sample t‐test was used for inter‐group comparison. Results The differences in the number of fixed segments, intraoperative bleeding, postoperative bed time, accuracy rate of pedicle screw placement, VAS, and ODI between the two groups were not statistically significant (p > 0.05). However, the operative time and total surgical incision length were significantly shorter in the WAPSF group than in the PPSF group (p < 0.05), and the FJV was significantly higher in the PPSF group than in the WAPSF group (p < 0.05). Also, the PPSF group received more intraoperative fluoroscopy (p < 0.05). The result of LCA and PAVBH in the WAPSF group were significantly better than in the PPSF group (p < 0.05). Conclusions Both PPSF and WAPSF were found to be safe and effective in the treatment of MSF without neurological deficits through our study. However, considering radiation exposure, FJV, vertebral height restoration, correction of kyphosis, and learning curve, WAPSF may be a better choice for neurologically intact MSF.